Remarks on Oligotoma saundersii (Westwood, 1837), an invasive species of Embioptera in Brazil - Montanuci, Pietra S. B.; Andrade, Bruna S.; Costa-Pinto, Paula J.; Rafael, José A.; Krolow, Tiago K. (Entomological Communications, 2023)
There are five families of Embioptera recorded in Brazil, namely: Anisembiidae, Archembiidae, Clothodidae, Teratembiidae, and Oligotomidae, the latter represented by Oligotoma saundersii (Westwood, 1837), an invasive species with worldwide distribution. In this work, we provide an update on O. saundersii distribution for three Brazilian states and the first record for Brazilian Amazon and Cerrado biomes. Additionally, we provide photographs of both sexes, a differential diagnosis for other families, and a distribution map with all records of O. saundersii for the country.